Performance enhancement of graphene-coated micro heat pipes for light-emitting diode cooling. (June 2020) - Gan, Jie Sheng; Yu, Hao; Tan, Ming Kwang; Soh, Ai Kah; Wu, Heng An; Hung, Yew Mun
Highlights: We integrate graphene nanocapillaries into micro heat pipes for LED cooling. Water transport and evaporation are synergically enhanced by nanocapillary action. Overall performance of graphene-coated micro heat pipe enhances significantly. Drastic temperature drop of LED leads to significant prolonged lifespan. Molecular dynamics simulations justify the ultrafast water transport in graphene. Abstract: The rate of water transport through graphene nanocapillaries is profoundly enhanced compared to that in microscale capillaries due to the prevalence of exceptionally high capillary pressures and large slip lengths. As an inaugural study, we integrate graphene nanocapillaries into a micro heat pipe (MHP) for enhanced light-emitting diode (LED) cooling. With the use of graphene nanocapillaries, the ultrafast water transport synergically enhances the water circulation and evaporation process in the microfluidic device. The graphene-coated MHP achieves more than 45% enhancement in the overall performance compared to the uncoated counterpart. In turn, the experiments demonstrate a drastic reduction of LED's operating temperature (more than 25 °C) which translates into a significantly prolonged lifespan of LED. The molecular dynamics simulations reveal that the oxygenated functional groups attached on graphene further increase the capillary pressure (~1000 bar) and effective velocity (~20 m/s) of the nanoconfined water, compared to those (~500 bar and ~10 m/s) in a pristine graphene nanochannel. The ultrafast water transport in graphene nanocapillary is justified. This study provides a holistic analysis and important insight into the phenomenon of ultrafast water transport in graphene nanocapillaries that exhibits an enormous potential in thermal energy management applications for LED cooling. Graphical abstract: Image, graphical abstract